Actividades ganaderas y su afección en la calidad del agua (microbiológica) para consumo humano en la comunidad de Julián - Mure Zambrano, Ronald José (2017)
The objective of this research was to determine the water quality of the micro basin of the Carrizal River, specifically in the community of Julián, using microbiological indicators, linking them with INEN regulations to establish their use in domestic consumption, moreover to the total coliform waters and Fecal samples were interrelated with TULSMA, to identify pretreatment of the water before being used in domestic consumption. In the study community, three sampling stations were established, making the two replicates at each point, in which the respective microbiological analyzes (total coliforms and fecal coliforms) were performed. Based on results and correlating them with the microbiological requirements for the use in the consumption according to the norm INEN was determined that the water coming from the slopes of Julián community shows a high contamination of both total coliforms and fecal coliforms that is they are not suitable for the human consumption if it is drunk in a direct way from water sources. Because of these waters were unfit for human consumption, the results obtained were also correlated with the microbiological requirements according to the TULSMA, identifying that the waters of this place should pass through a conventional treatment or disinfection in order to be consumed by the Inhabitants of this community.